Application of Acrostic Techniques to Improve Poetry Writing Skills - Ayu Herawati; Siti Isnaniah (SEAMEO QITEP in Language, 2022)
This classroom action research aims to improve students’ poetry text-writing skills. The technique used is the Acrostic Technique which can help students more easily come up with ideas in writing poetry texts. The results of the poetry text written with this technique also look unique. Students first write an exciting poem title. Furthermore, the title of this poem is written vertically and used as the first letter of each line of poetry written by students. This research was conducted on students of class X MIPA 2, SMA Negeri 2 Wates, Kulon Progo, Yogyakarta. Before taking action, the students’ initial abilities to write poetry were first measured, namely, the pre-action stage. In the pre-action, 0% of students scored more than 75. In the first cycle, the results showed that 17 out of 36 students or about 47.22% scored according to the success criteria. Students who were motivated during learning were as much as 25%. In cycle II, the results showed that more than 75% of students felt that learning to write poetry using the Acrostic Technique was interesting and fun. Students’ poetry writing skills improved after the Acrostic Technique was applied in cycle II. All students in cycle II scored more than 75 if the percentage was 100%. The criteria for the success of the action have been achieved in cycle II. The findings of this study are useful for students, teachers and schools in improving the quality of learning, especially improving writing skills.